PENGARUH MOTIVASI KERJA DAN KOMPETENSI TERHADAP PRESTASI KERJA GURU DI SMA NEGERI 08 KOTA LUBUKLINGGAU - Subuh Hidayat; Rizki Aprita Sari (Jurnal Media Ekonomi (JURMEK), 2017)
This study aims to describe the magnitude of the influence of work motivation and competence on teacher work performance in the State Senior High School 08 Lubuklinggau City. In this study using primary and secondary data sources, namely data collected by the author from the results of questionnaires and books and literature that are relevant to work motivation and competence and work performance. Based on the results of the research and discussion that the researcher did, it can be concluded that Based on the calculation results obtained the value of fcount = 44.475 greater than the value of ftabel = 3.33 and the probability (sig. 0.000) is smaller or less than 0.05, then Ha: Accepted and H0: Rejected. Which means that there is a significant effect of work motivation and teacher competence together on teacher work performance in SMA Negeri 08 Lubuklinggau City.teacher work performance in State High School 08 Lubuklinggau City. The results of this study are supported by the driving force that is in the teacher, a strong willingness to carry out the task well. Likewise with efforts to increase knowledge, skills and change attitudes, so that it can become the most valuable organizational wealth because with all its potential, employees can continue to be trained and developed, so that they can be more efficient and have optimal achievement in achieving organizational goals.